A brief overview of protest medicine - Matthew Anderson; Michael Cooper (Social Medicine Publication Group, 2013)
This paper was inspired by an important aspect of Victor W. Sidel's career that is not usually associated with an academic in medicine: his arrest record. Prominently displayed in Vic's office is a picture of a very determined (and somewhat younger) Vic Sidel being carried off in handcuffs by two policemen. The picture, taken in 1985 at an anti-apartheid protest, was published in The Nation's Health, the newspaper of the American Public Health Associa-tion. This was one of several arrests in Vic's career. As recently as 2012, Vic generously offered to be arrested as part of the Occupy Wall Street protests, citing his arrest record as qualification for this rather dangerous proposal.